The Prevalence, Characteristics, and Relationship of Risk Factors in Upper GI Tract Bleeding Patients Undergoing Endoscopy in Dr. Doris Sylvanis General Regional Hospital in 2019–2020 - Syahridho, Muhammad Andrean; Sasmithae, Lia; Carmelita, Austin Bertilova (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
Background: Upper gastrointestinal bleeding occurs in the lumen from the proximal section of the Treitz ligament. Furthermore, it is divided into variceal and non-variceal bleeding based on the etiology. The risk factors include age, smoking, alcohol, portal hypertension, hepatitis, and medications. Upper GI bleeding manifests as hematemesis and melena. This study aims to determine the prevalence, characteristics, and relationship of risk factors with upper GI bleeding in patients undergoing endoscopy in Dr. Doris Sylvanus General Regional Hospital Palangka Raya in 2019–2020.Method: An analytical observational study with a cross-sectional design is conducted using the patient’s medical record data.Results: The results showed that there were 72 patients with upper gastrointestinal bleeding, including 44 males and 28 females, accounting for 61.11% and 38.89%, respectively. About 47 patients had the highest age group, making up 65.28%, and the peptic ulcer was the most common etiology, occurring in 43 patients (59.72%). Also, the highest clinical manifestations and risk factors were melena in 47 patients (65.28%) and smoking in 32 patients (44.4%). The results of the bivariate analysis showed a significant relationship between upper GI bleeding and risk factors for certain drugs, portal hypertension, and hepatitis with a p-value of 0.013, 0.000, and 0.002.Conclusion: In this study, upper GI bleeding was the most common is a non-variceal bleeding, in men, age group under 60 years, with clinical manifestations of melena and there was a significant relationship between UGIB  with certain drugs, portal hypertension, and hepatitis.